KUALITAS PELAYANAN SERTIPIKASI PROYEK OPERASI NASIONAL AGRARIA (PRONA) DI KANTOR PERTANAHAN KABUPATEN DONGGALA - Saranga, Kartika Anna (Katalogis, 2016)
This Research Target is know and analyse the Service Quality of Sertipikasi Project Operate For The Agraria  National Agraria ( PRONA) in Land Ground Office of  Donggala  Regency Research Type is research qualitative with the informan selected by the four of people. Data collecting use the perception technique, interview and documentation. Technique analyse the data used by that is (1) Data collecting ( 2) Data Discount ( 3) Data Presentation ( 4) Verification ( 5) Conclusion. Theory used in this peneletian that is theory Parasuraman measuring Service quality: ( 1) Reliability ( 2) Responsivitas ( 3) Guarantee ( 4) Empathy ( 5) Direct Evidence. Pursuant to result of research and analysis done conducted by researcher in Office of Land Ground Office of Donggala Regency year 2015 concluded as follows: Quality of Project Service Operate For The National Agraria (PRONA) [in] Office of Land;Ground of Regency Donggala seen from factor of mainstay and factor Responsivitas not yet walked better, this matter is seen from result interview with informan in research location. Later;Then Quality of Project Service Operate For The National Agraria ( PRONA) in Office of Regency Land;Ground seen from factor of Guarantee and empathy factor and also from Direct Evidence factor have walked better. This matter is provable from result interview with informan in Donggala  Regency Donggala